THE EXECUTION OF JUDGMENTS OF THE EUROPEAN COURT OF HUMAN RIGHTS - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The European Court of Human Rights is considered as the most significant and most effective system of supervision in the field of international protection of human rights. It involves a supranational mechanism which enables the individuals to achieve their right on the international level. This mechanism of individual applications should overcome the discrepancy between the goals of international protection of human rights and execution of human rights norms at the state and local level. Successful and fast implementation of its judgments on the national level is of great importance for the Court, because the credibility and legitimacy of this system of protection depends on it. This paper will present the most significant aspects of execution and implementation of the judgments of the Court. The role of certain organs of the Council of Europe: Committee of Ministers, Parliamentary Assembly and the Court, in the procedure of execution of judgments, will be analyzed. Additionally, there will be presented the various manners in which the judgments are implemented and executed.